Absence of Borrelia Burgdorferi Antibodies in the Sera of Venezuelan Patients With Localized Scleroderma (Morphea) - Espinoza-León, Fabiola; Hassanhi-Hassanhi, Manzur; Arocha-Sandoval, Francisco; Urbina-López, Maricela (Investigación Clínica, 2009)
A possible association of Borrelia burgdorferi (Bb) with localized scleroderma (LS) has been postulated. However, the published data do not provide unequivocal results. Previous serologic analysis in LS patients in South American countries yielded positive results. The present study in our laboratory looked for evidence of Bb in LS patients in Venezuela, by antibacterial antibodies detection using the two-tiered approach as recommended by the Center for Disease Control and Prevention of Atlanta (United States). Twenty one serum samples from LS patients and twenty one samples from healthy individuals were analyzed. Four serum samples were ELISA positive: three from patients with LS and one from a healthy control. All ELISA positive samples were negative by IgG Western Blot. Our data do not support an association of Bb infection and the sclerotic lesions of LS; but do not rule out the possibility of a relationship between LS and an unknown geno-specie of Bb sensu lato complex, a different Borrelia specie or a different spirochetal organism, as the etiological agents of the skin lesions in the area